GENDER DIFFERENCES IN STRESS: WHY DO MEN AND WOMEN RESPOND TO STRESS DIFFERENTLY? - Shafa Shamil Nasibova (International Journal of Innovative Technologies in Social Science, 2026)
Stress has become a part of common human condition; stress-inducing factors surround us from all sides. The intensity of life has increased dramatically in recent decades, requiring a completely different speed of decision-making and action.Stressful situations place increased demands on a person, causing psychophysical, emotional, psychological, energetic, and intellectual strain. Stress causes physiological and psychological changes in a person and can accumulate and negatively impact their physical and mental health. When considering strategies and behavioral patterns in stressful situations, it is important to consider gender, as men and women react differently to stress. The most common signs of stress-related health problems include headaches, sleep disturbances, difficulty concentrating, irritability, gastrointestinal problems, job dissatisfaction, lack of energy, low morale, depression, and intense anxiety that sometimes manifests as panic attacks. These can develop into psychiatric disorders requiring treatment.The aim of the study is to learn the stress differences in both of the genders. The next purpose of the paper is to search for assessment tools and measurement scales that are effective, valid and reliable in this field.